Geomorphology, Stratigraphy and 14C-Chronology of Ancient Tufas at Louie Creek, Northwest Queensland, Australia - Drysdale, Russell; Head, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1994)
ABSTRACTLouie Creek is a karst spring-fed stream situated in the seasonally humid tropics of northwest Queensland, Australia. It rises as a series of small exsurgences along the eastern edge of the Barkly Tableland. As it enters the lowlands of the Carpentaria plain, the creek deposits tufa which produces a series of cascades. This modern tufa extends discontinuously for about 1.5 km. A series of ancient tufas, in places lying adjacent to sites of modern deposition, extends discontinously for about 8 km downstream. At least two ancient tufa units are preserved at one location, Little lndarri site. The older unit comprises a sequence of well-preserved barrages with an orientation transverse to present-day stream flow. In places, erosion has reduced these barrages to their calcrete substrate. The older tufa is overlain in places by sediment which has become cemented to form a second calcrete unit. This sediment is in turn succeeded by the younger ancient tufa. Subsequent river incision has removed part of the sediment from the older unit and exposed several contact points between the ancient tufa and calcrete units. Radiocarbon dating of the Little lndarri site tufas, as well as other ancient Louie Creek units, yielded apparent ages ranging from ~ 30 to ~ 14 ka BP, suggesting that conditions were sufficiently wet during the period immediately preceding and throughout the Last Glacial Maximum for tufa depostion to occur. However, ancient tufa formation occurred during a phase of net river aggradation. There is geomorphic evidence that such aggradation was a result of an increased sediment supply to the fluvial system, most likely in response to conditions drier than present. Results from studies elsewhere in the region support such a Late Pleistocene trend. Incision of Louie Creek, which postdates the youngest of the dated ancient tufas, is most likely to have resulted from a shift to wetter conditions during the early Holocene,